Prognostic value of immunohistochemical expression of HER-2/neu in patients with lung carcinoma - Ilievska Poposka, Biljana; Smichkoska, Snezhana; Simonida Jovanovska Crvenkovska; Zafirova Ivanovska, Beti; Stefanovski, Tome; Petrushevska, Gordana (Association of Radiology and Oncology, 2008)
Background. The amplification and the overexpression of the Her-2/neu gene have been shown in certain human tumours and are postulated to be important in human carcinogenesis. In this study we evaluated the expression of HER-2/neu gene in patients with lung carcinoma (LC) and assessed its prognostic significance. Patients and methods. HER-2/neu expression was determined in 127 LC patients using immunohistochemistry (IHC) performed on paraffin-embedded section – Hercep TestTM (DAKO). Results. The overall HER-2/neu expression was seen in 36 (28.35%) of 127 LC patients. According to the histological type, HER-2/neu overexpression was detected in 12 patients with adenocarcinomas (60%), in 19 patients with squamous cell carcinomas (31.14%), in 4 patients with small cell-lung carcinomas (10%) and in 1 patient with other carcinomas (16.66%). Only in patients with small cell-lung carcinomas HER-2/ neu overexpression was in correlation with the stage of the disease (p<0.001). The patients with HER-2/neu positive expression were associated with a significantly shorter survival compared with those who were HER-2/neu negative (log rank, p<0.002). Conclusions. These observations suggest that HER-2/neu positivity may serve as a prognostic indicator in patients with LC. HER-2/neu plays a role in identifying patients at risk for the shortened survival, who may benefit from a more aggressive therapy. Key words: HER-2/neu, lung cancer; immunohistochemisty; survival
Keywords: HER-2/neu; lung cancer; immunohistochemisty; survival